2016
DOI: 10.1177/1534735416668257
|View full text |Cite
|
Sign up to set email alerts
|

A Mindfulness-Based Lifestyle Intervention for Obese, Inactive Endometrial Cancer Survivors: A Feasibility Study

Abstract: Background: Mindfulness-based interventions (MBIs) to address self-regulation and lifestyle behaviors (diet, physical activity) may benefit endometrial cancer survivors (ECS), who are at increased risk for morbidity and mortality associated with obesity. However, the acceptability of mindfulness training and whether it can augment behavior change in ECS is unknown. We aimed to examine; 1) the feasibility of the Mindfulness in Motion + Diet (MIM+D) intervention and 2) the preliminary efficacy of MIM+D for impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 65 publications
0
23
0
7
Order By: Relevance
“…Of the 20 MBIs, three cohort studies and five RCTs showed significant positive between‐subjects effects on PA. Three studies showed significant positive within‐subjects effects on PA but found no differences between the MBI and a control group . Two cohort studies and two RCTs showed positive effects for some PA outcomes. Three RCTs found no effect on PA outcomes in either group , and two RCTs showed better outcomes following the standard intervention than the MBI .…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Of the 20 MBIs, three cohort studies and five RCTs showed significant positive between‐subjects effects on PA. Three studies showed significant positive within‐subjects effects on PA but found no differences between the MBI and a control group . Two cohort studies and two RCTs showed positive effects for some PA outcomes. Three RCTs found no effect on PA outcomes in either group , and two RCTs showed better outcomes following the standard intervention than the MBI .…”
Section: Resultsmentioning
confidence: 96%
“…Of the 20 studies that employed a MBI to target PA, five were cohort studies (no control group) , one was a non‐randomized controlled clinical trial and 14 were RCTs . Five studies compared usual care with a mindfulness component to a usual care‐only group ; eight studies compared a MBI with another intervention ; and two studies compared a MBI with a no‐treatment control group .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations